The Effect of Online-Based Disctance Learning on Student Learning Outcomes at PAI Lessons at SMA Negeri 5 Bogor - Turohmah, Fauzia; Lisnawati, Santi (SYAMIL: Journal of Islamic Education, 2021)
Online-based distance learning is an alternative to learning in the current situation. Distance Education is an education whose students are separated from educators, and their learning uses a variety of learning resources through communication technology, internet information and other media. This study aims to find out how much influence online-based distance learning has on students' learning outcomes in PAI. The research method used is expost facto research. This type of pining is with primary data and secondary data. The results showed that; Online-based Distance Learning positively and signification of student learning outcomes by 13.3%. Online-based Distance Learning can improve the quality of education in order to continue to be carried out properly, especially in student learning outcomes even in the condition of the covid-19 pandemic.